Biodiversity and Conservation of the Estuarine and Marine Ecosystems of the Venezuelan Orinoco Delta - Miloslavich, Patricia; Martín, Alberto; Klein, Eduardo; Díaz, Yusbelly; Lasso, Carlos A.; Cárdenas, Juan José; Lasso-Alcala, Oscar M. (IntechOpen, 2011)
None